2004
DOI: 10.1093/jee/97.2.628
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the European Union Maize Landrace Core Collection for Resistance to Sesamia nonagrioides (Lepidoptera: Noctuidae) and Ostrinia nubilalis (Lepidoptera: Crambidae)

Abstract: Two corn borer species are the principal maize insect pests in Europe, the European corn borer, Ostrinia nubilalis (Hübner), and the pink stem borer, Sesamia nonagrioides (Lefebvre). Hence, it would be advisable to evaluate the European maize germplasm for corn borer resistance to generate European varieties resistant to corn borer attack. The creation of the European Union Maize Landrace Core Collection (EUMLCC) allowed the screening of most of the variability for European corn borer resistance present among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…These results support the importance of the evaluation of new materials because they can improve the level of resistance already achieved. Similarly, Malvar et al (2004) found some corn landraces that improved stem resistance to corn borers compared to that reported by Malvar et al (1993).There was a significant and negative relationship between percentage of stem damaged and days to silking ( (Tables 1 and 3). The other hybrid (EP79 × W552) which involves the inbred EP79 developed by selection for resistance to pink stem borer, differed significantly from A661 × EP42, described as tolerant in a previous work , for stem and ear damage, but did not differ for yield under pink stem borer infestation.…”
supporting
confidence: 55%
“…These results support the importance of the evaluation of new materials because they can improve the level of resistance already achieved. Similarly, Malvar et al (2004) found some corn landraces that improved stem resistance to corn borers compared to that reported by Malvar et al (1993).There was a significant and negative relationship between percentage of stem damaged and days to silking ( (Tables 1 and 3). The other hybrid (EP79 × W552) which involves the inbred EP79 developed by selection for resistance to pink stem borer, differed significantly from A661 × EP42, described as tolerant in a previous work , for stem and ear damage, but did not differ for yield under pink stem borer infestation.…”
supporting
confidence: 55%
“…Hopefully, Oroso su1 will show improved survival under cold conditions compared to su1 controls; Revilla et al (1998) indicates that Oroso can improve the ability of some su1 inbreds to germinate and survive under cold conditions. Rastrojero might be able to supply a trait missing in these hybrids: resistance to ear damage by corn borers (Malvar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, Rastrojero is well adapted to the conditions of Spain's interior and could be a promising source of adaptation traits for sweetcorn in this region; it could also help to improve sweetcorn resistance to corn borers (Malvar et al, 1993(Malvar et al, , 2004. Resistance to corn borers is required in both regions since ear damage by the corn borer, the European corn borer (Ostrinia nubilalis Hubner) and the pink stem borer (Sesamia nonagrioides Lef.…”
Section: Introductionmentioning
confidence: 99%
“…Practical breeding research using landraces has been carried out in several crops, e.g. rice (Hargrove and Cabanilla 1979), maize (Malvar et al 2004), legumes (Isemura et al 2001, Zhang et al 2009) as well as wheat. For bread wheat (Triticum aestivum L.) the importance of landraces is more critical than for other crops because it does not have a direct wild ancestor with the same genomic constitution due to its hybrid origin (Kihara 1944, McFadden andSears 1946).…”
Section: Introductionmentioning
confidence: 99%